Soil greenhouse gas emissions and their relations to soil attributes in a sugarcane area - Bicalho, Elton da Silva [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
The production of the main soil greenhouse gases (GHG: CO2, CH4 and N2O) is influenced by agricultural practices that causes changes in soil phys¬ical, chemical and biological attributes, directly affecting their emission to the atmos¬phere. The aim of this study was to investigate the infield soil CO2 emissions (FCO2) and the soil CO2, CH4 and N2O production potentials (PCO2, PCH4 and PN2O, respec¬tively) in laboratory conditions, and their relationship to soil attributes in a mechanically harvested sugarcane area. The experimental area consisted of a 50 × 50-m radially symmetrical grid containing 133 points spaced at minimum distances of 0.5 m in the center of the sample grid. It was carried out eight evaluations of FCO2, soil temperature and soil moisture over a period of 19 days. Soil physical and chemical attributes were determined by sampling at a depth of 0–10 cm. The quantification of PCO2, PCH4 and PN2O consisted of laboratory incubation and determination of gas concentration by gas chromatography. FCO2 presented an infield average emission value of 1.19 µmol CO2 m−2 s−1, while GHG production in laboratory was 2.34 µg C–CO2 g−1 d−1 and 0.20 ng N–N2O g−1 d−1 for PCO2 and PN2O, respectively. No significant production or oxidation was observed for CH4. The factor analysis showed the formation of two independent processes that explained almost 72% of the total variance observed in the data. The first process was related to the transport of FCO2 and its relation to soil physical attrib¬utes, such as microporosity, macroporosity, the C/N ratio, soil moisture and soil bulk density, showing the dependence between FCO2 and soil porosity. The second process was related to the soil CO2 and N2O production potentials in laboratory conditions and their relation to soil chemical attributes, such as sum of bases, pH and available phos¬phorus, which affects the microbial activity and contributes to the GHG production. Although presented as independent, these processes are coupled and occur simulta¬neously in the soil, in addition to provide information about their variability, showing if the infield emissions are due to the gas transport processes or to soil carbon levels and their quality. Furthermore, the spatial dependence of FCO2 is related to soil poros¬ity, as well as the spatial dependence of PCO2 and PN2O is related to soil chemical attributes. In addition, anisotropy occurred mainly under infield conditions, mostly for the attributes related to soil porosity since disturbed soils used under laboratory con-ditions lose their structure and hence the effect of the management found under infield conditions.

A produção dos principais gases de efeito estufa (GEE: CO2, CH4 e N2O) é influenciada por práticas agrícolas que causam alterações nos atributos físi¬cos, químicos e biológicos do solo, afetando diretamente sua emissão para a atmos¬fera. O objetivo deste estudo foi investigar a emissão de CO2 do solo (FCO2) em con¬dições de campo e a produção potencial de CO2, CH4 e N2O do solo (PCO2, PCH4 e PN2O, respectivamente) em condições de laboratório, além de suas relações com os atributos do solo em uma área de cana-de-açúcar colhida mecanicamente. A área experimental constituiu-se de um gradeado simétrico radialmente de 50 × 50 m con-tendo 133 pontos espaçados em distâncias mínimas de 0,5 m no centro da malha amostral. Foram conduzidas oito avaliações para FCO2, temperatura e umidade do solo durante um período de 19 dias. Os atributos físicos e químicos do solo foram determinados por meio de amostragem na profundidade de 0–10 cm. A quantificação de PCO2, PCH4 e PN2O consistiu de incubação em laboratório e determinação da con¬centração dos gases por meio de cromatografia gasosa. FCO2 apresentou um valor de emissão média de 1,19 µmol CO2 m−2 s−1, enquanto a produção de GEE em laborató¬rio foi de 2,34 µg C–CO2 g−1 d−1 e 0,20 ng N–N2O g−1 d−1 respectivamente para PCO2 e PN2O. Não foi observada produção ou oxidação significativa de CH4. A análise de fatores mostrou a formação de dois processos independentes que explicaram quase 72% da variância total observada nos dados. O primeiro processo foi relacionado ao transporte de FCO2 em campo e sua relação com atributos físicos do solo, tais como microporos, macroporos, relação C/N, umidade e densidade, mostrando a dependên¬cia entre FCO2 e a porosidade do solo. O segundo processo foi relacionado à produção potencial de CO2 e N2O do solo em condições de laboratório e sua relação com atri¬butos químicos do solo, tais como soma de bases, pH e fósforo disponível, os quais afetam a atividade microbiana e contribuem para a produção de GEE. Embora apre¬sentados como independentes, esses processos estão relacionados e ocorrem simul¬taneamente no solo, fornecendo informações sobre sua variabilidade e mostrando se as emissões em campo são devidas aos processos de transporte de gás ou aos níveis de carbono no solo e sua qualidade. Além disso, a dependência espacial de FCO2 está relacionada à porosidade do solo, assim como a dependência espacial de PCO2 e PN2O está relacionada aos atributos químicos do solo. Adicionalmente, foi observada aniso-tropia principalmente em condições de campo, principalmente para os atributos rela-cionados à porosidade do solo, já que o solo pulverizado utilizado no laboratório perde sua estrutura e, consequentemente, o efeito do manejo encontrado em condições de campo.
Emissão de gases de efeito estufa e sua relação com atributos do solo em área de cana-de-açúcar
Keywords: Carbon dioxide; Methane; Nitrous oxide; Production potentials; Soil respiration; Gas transport; Dióxido de carbono; Metano; Óxido nitroso; Produção potencial; Respiração do solo; Transporte gasoso